Effects of International Institutional Factors on Earnings Quality of Banks - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2010)
We examine the relation between legal, extra-legal and political institutional factors and earnings quality of banks across countries. We predict that earnings quality is higher in countries with legal, extra-legal and political systems that reduce the consumption of private control benefits by insiders and afford outside investors greater protection. Using a sample of banks from 29 countries over the period from 1993 to 2006, we find all five measures of earnings quality studied are higher in countries with stronger legal, extra-legal and political institutional structures. Our findings highlight the implications of institutional environments for financial reporting quality and are relevant to bank regulators who are considering additional regulations on bank financial reporting.